PENGARUH MODEL PROJECT BASED LEARNING TERHADAP AKTIVITAS BELAJAR DAN KETERAMPILAN PROSES SAINS SMA NEGERI 6 METRO - Andriani, Sima; Suseno, Nyoto; Alarifin, Dedy Hidayatullah (JURNAL FIRNAS, 2023)
The aim of this research was to determine the influence of the project based learning model on the learning activities of class XI students at SMA Negeri 6 Metro, to determine the influence of the project based learning model on the science process skills of class This research was conducted using a true experimental design. Determining the sample using the cluster random sampling technique selected was class XI 1 as the experimental class, class XI 4 as the control class. The data collection technique used was an observation sheet to measure learning activities and science process skills in the experimental class and control class. The observation instrument used is a grid of observation sheets. To test and analyze the hypothesis in this research, the independent t-test was used. The results of the research show the influence of the project based learning model on the learning activities of class XI SMA Negeri 6 Metro, namely the significance obtained by the Sig value. equal to 0.000 < 0.05. There is an influence of the project based learning model on the science process skills of class XI SMA Negeri 6 Metro, namely on the significance obtained by the Sig value. equal to 0.000 < 0.05. From the research carried out, it can be concluded that there is a positive influence of the use of the project based learning model on learning activities as shown by the results of the hypothesis test, the significance value obtained is Sig. equal to 0.000 < 0.05. There is a positive influence of using the project based learning model on science process skills, as shown by the results of the hypothesis test, the significance value obtained is Sig. of 0.000 < 0.05.